2020
DOI: 10.1177/0963689720932142
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Injection of Cell-laden 3D Microcryogels Empower Low-dose Cell Therapy for Osteoarthritis in a Rat Model

Abstract: Intra-articular injection of mesenchymal stem cells (MSCs) in an osteoarthritic joint can help slow down cartilage destruction. However, cell survival and the efficiency of repair are generally low due to mechanical damage during injection and a high rate of cell loss. We, thus, investigated an improved strategy for cell delivery to an osteoarthritic joint through the use of three-dimensional (3D) microcryogels. MSCs were seeded into 3D microcryogels. The viability and proliferation of MSCs in microcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
0
28
0
1
Order By: Relevance
“…The 3D reconstructed images were evaluated and visualized using Inveon Research Workplace (Siemens) software. A semiquantitative method using the degree of osteophytes and joint destruction was introduced to grade the degree of OA changes [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D reconstructed images were evaluated and visualized using Inveon Research Workplace (Siemens) software. A semiquantitative method using the degree of osteophytes and joint destruction was introduced to grade the degree of OA changes [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…When packed into a geometrically confined 3D environment, the microniches may further self-assemble into functional 3D constructs [ 30 ]. We have shown that these injectable 3D microniches can increase the efficiency of cell therapy, whereby a low cell dose delivered within microniches can achieve similar effects as a high cell dose delivered directly in rat models of knee OA [ 31 ] and critical limb ischemia [ 28 ]. However, we have not optimized the methods for the efficient production of cell-laden microniches that would be suitable for scale-up applications, or the functionality of the microniches to ideally substitute for both high-dose cell injection and repeated injections.…”
Section: Introductionmentioning
confidence: 99%
“…One potential method to address this problem is to increase the survival, retention, and function of MSCs by injecting them through a delivery vehicle. For instance, we previously showed that MSCs delivered through 3D microscopic hydrogels could achieve longer term therapeutic effects in a rat OA model, even when a reduced cell dose was used [ 15 ]. Nevertheless, such delivery methods require additional prior processing of MSCs, as well as encapsulation and possibly pre-culturing of the MSCs in the delivery vehicle before injection, which may lead to a more extended or complex preparation and limited shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that stem cells provide a temporary/early-stage effect rather than prolonged effectiveness in treating OA, indicating the need for higher cell numbers and multiple cell injections. The short-term effects of stem cells are mainly due to limited long-term cell survival/retention, extensive cell death and poor cellular function, and inadequate cellular distribution following injection in the target site ( 17 ). To overcome these challenges, large doses of cells and multiple injections have been tried; however, these approaches are not economically viable and are associated with the risk of cell overexpansion ( 17 ).…”
mentioning
confidence: 99%
“…retention, extensive cell death and poor cellular function, and inadequate cellular distribution following injection in the target site (17). To overcome these challenges, large doses of cells and multiple injections have been tried; however, these approaches are not economically viable and are associated with the risk of cell overexpansion (17).…”
mentioning
confidence: 99%